Employment and Hours over the Business Cycle in a Model with Search Frictions - Noritaka Kudoh; Hiroaki Miyamoto; Masaru Sasaki (Institute for the Study of Labor (IZA), 2015)
This paper studies a labor market search-matching model with multi-worker firms to investigate how firms utilize the extensive and intensive margins over the business cycle. The earnings function derived from the Stole-Zwiebel bargaining acts as an adjustment cost function for employment and hours. We calibrate the model to match the Japanese labor market, in which the intensive margin accounts for 79% of the variations in total working hours. The model replicates the observed cyclical behavior of hours of work, but fails to generate employment volatility of realistic magnitude. Additional penalties for longer hours of work do not resolve this issue. Wage rigidity and persistent shocks are promising lines of further investigations.
Keywords: E32; J20; J64; 330; multi-worker firms; search; hours of work; business cycles